1994
DOI: 10.1128/aac.38.9.2086
|View full text |Cite
|
Sign up to set email alerts
|

Antiprotozoal activities of benzimidazoles and correlations with beta-tubulin sequence

Abstract: Benzimidazoles have been widely used since the 1960s as anthelmintic agents in veterinary and human medicine and as antifungal agents in agriculture. More recently, selected benzimidazole derivatives were shown to be active in vitro against two protozoan parasites, Trichomonas vaginalis and Giardia lamblia, and clinical studies with AIDS patients have suggested that microsporidia are susceptible as well. Here, we first present in vitro susceptibility data for T. vaginalis and G. lamblia using an expanded set o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
107
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(117 citation statements)
references
References 26 publications
3
107
0
2
Order By: Relevance
“…This indicates that cytotoxic effects of ABZ (or its metabolites) due to tubulin depolymerization may be hampered in Echinococcus by: (1) the presence of an ABZ-insensitive b-tubulin complementing the sensitive isoform; (2) rapid ABZ catabolism; (3) toxicity of ABZ catabolites rather than ABZSO itself; and/or (4) a good regenerative power due to insensitive stem cells. Sensitivity of mammalian cells (carrying the benzimidazole-resistant allele 200-Tyr) lies between an IC 50 around 0.25 mM in HL60 cells and 20 mM in Vero cells (nocodazole, another benzimidazole, is, however, 10-to 20-fold more toxic; Katiyar et al, 1994). This suggests that ABZ may also bind with low affinity to mammalian b-tubulin, and/or the existence of another, unknown, mode of action of ABZ that may be responsible for ABZ side-effects in patients, as mentioned above.…”
Section: Mode Of Action Of Benzimidazolesmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that cytotoxic effects of ABZ (or its metabolites) due to tubulin depolymerization may be hampered in Echinococcus by: (1) the presence of an ABZ-insensitive b-tubulin complementing the sensitive isoform; (2) rapid ABZ catabolism; (3) toxicity of ABZ catabolites rather than ABZSO itself; and/or (4) a good regenerative power due to insensitive stem cells. Sensitivity of mammalian cells (carrying the benzimidazole-resistant allele 200-Tyr) lies between an IC 50 around 0.25 mM in HL60 cells and 20 mM in Vero cells (nocodazole, another benzimidazole, is, however, 10-to 20-fold more toxic; Katiyar et al, 1994). This suggests that ABZ may also bind with low affinity to mammalian b-tubulin, and/or the existence of another, unknown, mode of action of ABZ that may be responsible for ABZ side-effects in patients, as mentioned above.…”
Section: Mode Of Action Of Benzimidazolesmentioning
confidence: 99%
“…Molecular genetics revealed that sensitivity to benzimidazoles in evolutionary distant organisms such as fungi, nematodes, platyhelmithes and various protozoa was correlated with the presence of specific alleles of b-tubulin genes (Driscoll et al, 1989;Katiyar et al, 1994;Kwa et al, 1995;Henriquez et al, 2008), the substitution of Phe to Tyr in position 200 being sufficient for switching from benomyl sensitivity to resistance in nematodes (Kwa et al, 1995). Molecular modelling of the putative ABZ binding site in ABZ-resistant Acanthamoeba b-tubulin revealed 13 residues, four of which showed sequence variation as compared to tubulins of sensitive organisms.…”
Section: Mode Of Action Of Benzimidazolesmentioning
confidence: 99%
“…Benzimidazoles have been widely used since the 1960s as anthelmintic agents in veterinary and human medicine and as antifungal agents in agriculture [8]. The target site of benzimidazole anthelmintic is β-tubulin which is indispensable to form microtubules, responsible for vital cell functions as motility, cellular shape, mitosis, coordination, transport and secretion in nematodes, cestodes and fluke [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of benzimidazoles are in used, like Thiabendazole, Flubendazole (antihelminthic), Omeprazole, Lansoprazole (anti-ulcerative) and Astemizole (anti-histaminic). The chemistry and pharmacology of benzimidazoles have been of great interest to medicinal chemistry [7,8] , because of its derivatives possessed various biological activities such as anti-oxidant [9,10], anti-microbial [11][12][13][14][15][16] , antihelmentic [17][18][19], anti-cancer [20], anti-hypertensive [21], anti-neoplastic [22], anti-inflammatory [23,24], analgesic [25], anti-protozoal [26,27], anti hepatitis activities [28] and also shows anti-depressant activity [29].…”
Section: Introductionmentioning
confidence: 99%